THE EFFECT OF SUPEROVULATION INDUCTION USING FSH ON INCREASING FSH AND LH CONCENTRATIONS IN NEW ZEALAND WHITE RABBITS - Wahyuni, Sri; Fathurrahman, Fadhil; Adam, Mulyadi; Syafruddin, Syafruddin; Roslizawaty, Roslizawaty; Hasan, Muhammad; Melia, Juli; Dasrul, Dasrul; Isa, Muhammad; Rosmaidar, Rosmaidar (Universitas Syiah Kuala, 2024)
This study aimed to determine the concentrations of Follicle Stimulating Hormone (FSH) and Luteinizing Hormone (LH) in New Zealand White (NZW) rabbits after superovulation induction using FSH. Six female NZW rabbits and one male NZW rabbit were used in this study. Criteria for female NZW rabbits used include having previously given birth, not being pregnant, and having a body weight of 2-3 kg. The rabbits were divided into two treatment groups; the first group was injected with physiological NaCl (NZW1, n= 3), while the second group was injected with FSH (NZW2, n= 3). Injections of physiological NaCl or FSH were administered five times at 12-hour intervals and first injection was given at 20:00 p.m. In NZW1, each injection was given physiological NaCl with volumes of 0.2:0.2+0.2;0.4+0.4 mL, respectively whereas in NZW2, each injection was given FSH with doses of 4:4+4:8+8 mg, respectively. Twelve hours after the last FSH injection, NZW2 rabbits were injected with 100 IU hCG and mated with male rabbit, while NZW1 rabbits were mated without hCG administration. On days 1, 3, and 5 after mating, blood samples were collected for FSH and LH hormone examination using the Enzyme-Linked Immunosorbent Assay (ELISA) method. The FSH concentrations on days 1, 3, and 5 between NZW1 vs NZW2 were 34.781.46 vs 39.753.18; 41.434.90 vs 41.425.14; and 44.471.51 vs 30.130.19 mIU/mL, respectively (P0.05). The LH concentrations on days 1, 3, and 5 between NZW1 vs NZW2 were 33.784.01 vs 40.1812.36; 29.342.24 vs 31.3110.13; and 42.0911.38 vs 30.578.87 mIU/mL, respectively (P0.05). It is concluded that FSH administration does not affect the concentrations of FSH and LH in NZW rabbits. The FSH concentration five days after mating tends to fluctuate, while the LH concentration tends to decrease as the days increased.